ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN KRITERIA WATSON PESERTA DIDIK KELAS XII IPS SMA NEGERI 4 BUKITTINGGI - Refenia Usman (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematics is implemented in various fields of science. However, there is still many students who make many mistakes in solving math problems. Therefore, an analysis of these errors is necessary to apply. This research aims to describe the types and factors which cause students to make errors according to Watson's criteria, namely incorrect data (ID), inappropriate procedures (IP), omitted data (OD), omitted conclusion (OC), response level conflicts (RLC), undirected manipulation (IM), skill hierarchy problems (SHP), and above other (AO). This research itself implements descriptive. Next, 34 students in twelfth-grade social science of SMA Negeri 4 Bukittinggi in the academic year 2020/2021 had participated in the research, and five of them were chosen to be interviewed. The research data were obtained from the test, interviews, and documentation. The data analysis technique was carried out using data reduction, data presentation, and data verification. The results showed that the most dominant type of error is AO which is 33.82%. Furthermore, RLC error is 25.55%, SHP error is 7.90%, IP error is 5.51%, ID error is 5.33%, the OD error is 4.96%, IM error is 4.04%, and OC error is 1.84%. These errors were caused by a lack of understanding about the material, inaccuracy, lack of experience and preparation before carrying out the test. Keywords—Watson Error Analysis, Mathematical Problems